THE DECLINE IN VIABILITY OF CORN SEEDS (INBRED LINES) UNDER INFLUENCE OF THE STORAGE DURATION IN “OPEN WAREHOUSE” - Borza, Gavrilă (2018)
The objective of this research was to determine the changes in quality of maize (Zea mays L.) seed in three years storage and in four genetically different Inbred Lines, during storage, under open storage conditions. The complexity of producing inbred lines to produce hybrids with a number of attributes such as adaptability, disease resistance and drop, high production potential has in practice led to them being produced in quantities to meet the needs over many years, therefore subject to longer shelf life. Four experimental Inbred lines, each represented by four seed lots produced by the Agricultural Research and Development Station Turda, /Romania, were evaluated. Seeds (untreated) were stored for 36 months, under open storage conditions and for the seed performance was evaluated the time of “initial-phase” and every 12 months by seed viability (germination). The experimental results show a large variation of the recorded germination, both in the line with the duration of the storage, but also between them, in each analyzed stage. After a 36-month retention period, they recorded very low germination values, for example, the LC363 line had the final germination of G36 = 33%, fact that highlights the different conservation capacity of each seed's initial traits and that this is a genetic feature, influenced differently by the duration and conditions of retention